(-1-2m)(5-3m)=

Simple and best practice solution for (-1-2m)(5-3m)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-1-2m)(5-3m)= equation:


Simplifying
(-1 + -2m)(5 + -3m) = 0

Multiply (-1 + -2m) * (5 + -3m)
(-1(5 + -3m) + -2m * (5 + -3m)) = 0
((5 * -1 + -3m * -1) + -2m * (5 + -3m)) = 0
((-5 + 3m) + -2m * (5 + -3m)) = 0
(-5 + 3m + (5 * -2m + -3m * -2m)) = 0
(-5 + 3m + (-10m + 6m2)) = 0

Combine like terms: 3m + -10m = -7m
(-5 + -7m + 6m2) = 0

Solving
-5 + -7m + 6m2 = 0

Solving for variable 'm'.

Factor a trinomial.
(-1 + -2m)(5 + -3m) = 0

Subproblem 1

Set the factor '(-1 + -2m)' equal to zero and attempt to solve: Simplifying -1 + -2m = 0 Solving -1 + -2m = 0 Move all terms containing m to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2m = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2m = 0 + 1 -2m = 0 + 1 Combine like terms: 0 + 1 = 1 -2m = 1 Divide each side by '-2'. m = -0.5 Simplifying m = -0.5

Subproblem 2

Set the factor '(5 + -3m)' equal to zero and attempt to solve: Simplifying 5 + -3m = 0 Solving 5 + -3m = 0 Move all terms containing m to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3m = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3m = 0 + -5 -3m = 0 + -5 Combine like terms: 0 + -5 = -5 -3m = -5 Divide each side by '-3'. m = 1.666666667 Simplifying m = 1.666666667

Solution

m = {-0.5, 1.666666667}

See similar equations:

| x+3y=776 | | 7y+2=51 | | 12x^2-16x-3=0 | | 5a^2+24a-5= | | x+y=250 | | 2x-9=-8 | | 2*-9=-8 | | 3p^2=-4p-1 | | 3x^2=4x+11 | | 2x+5y=1252x-y-10 | | 2x+5y=125 | | -4y=12x+13 | | 30*8.50*52= | | -4x-6+x=-2x-x-10 | | y^2=-27 | | 8x-51=10x-57 | | 6x+1-3=2x+4(1+x) | | -8m^2-8n^2=-40 | | 6(25-x)+10=-15x+242 | | -z+7z=-7z-5+4z | | b^2+5bd-14d^2= | | 0=y^3-4y | | 5(4x-4)-1=20x-21 | | b^2-4b-14=2 | | 9x-4=6x+17 | | 8-5x-5-5x=5 | | 45.8+18.3(15.1-16.1)= | | 3x+14=9x-4 | | -5x+3(x+8)=16-2x | | -(2x-1)+3x=4x-5 | | 6x+6y=o | | 3x+8+3x-2=180 |

Equations solver categories